The US Food and Drug Administration's expedited approval programs: Evidentiary standards, regulatory trade-offs, and potential improvements. (June 2018) - Wallach, Joshua D; Ross, Joseph S; Naci, Huseyin
The US Food and Drug Administration has several regulatory programs and pathways to expedite the development and approval of therapeutic agents aimed at treating serious or life-debilitating conditions. A common feature of these programs is the regulatory flexibility, which allows for a customized approval approach that enables market authorization on the basis of less rigorous evidence, in exchange for requiring postmarket evidence generation. An increasing share of therapeutic agents approved by the Food and Drug Administration in recent years are associated with expedited programs. In this article, we provide an overview of the evidentiary standards required by the Food and Drug Administration's expedited development and review programs, summarize the findings of the recent academic literature demonstrating some of the limitations of these programs, and outline potential opportunities to address these limitations. Recent evidence suggests that therapeutic agents in the Food and Drug Administration's expedited programs are approved on the basis of fewer and smaller studies that may lack comparator groups and random allocation, and rather than focusing on clinical outcomes for study endpoints, rely instead on surrogate markers of disease. Once on the market, agents receiving expedited approvals are often quickly incorporated into clinical practice, and evidence generated in the postmarket period may not necessarily address the evidentiary limitations at the time of market entry. Furthermore, not all pathways require additional postmarket studies. Evidence suggests that drugs in expedited approval programs are associated with a greater likelihood that the Food and Drug Administration will take a safety action following market entry. There are several opportunities to improve the timeliness, information value, and validity of the pre- and postmarket studies of therapeutic agents receiving expedited approvals. When use of nonrandomized and uncontrolled studies cannot be avoided prior to market entry, randomized trials should be mandatory in the postmarket period, unless there are strong justifications for not carrying out such studies. In the premarket period, validity of the surrogate markers can be improved by more rigorously evaluating their correlation with patient-relevant clinical outcomes. Opportunities to reduce the duration, complexity, and cost of postmarket randomized trials should not compromise their validity and instead incorporate pragmatic "real-world" design elements. Despite recent enthusiasm for widely using real-world evidence, adaptive designs, and pragmatic trials in the regulatory setting, caution is warranted until large-scale empirical evaluations demonstrate their validity compared to more traditional trial designs.